PERLINDUNGAN HUKUM HAK ATAS TANAH ULAYAT MASYARAKAT HUKUM ADAT DI KABUPATEN MALUKU TENGGARA. - Welerubun, Cornelia Junita (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
Unalienated land dispute resolution in a way that is custom done by indigenous chiefs to resolve the dispute relating to customs. To resolve the disputes of indigenous chiefs hold a customary or sitting often known as judicial customs. The judicial nature of the Customs mediation, there is King as a mediator in it. The important role of indigenous chiefs of in dispute resolution is needed, this is because Community law is very respectful of indigenous chiefs. Legal protection must be viewed stages namely legal protection was born from a provision of the law and the rule of law given by a society that basically is the community's agreement to regulate the relationship between the behavior members of the society and between the individuals with the Government deemed to represent the interests of the community. Legal protection is not a true picture of the work function of the law itself that its purpose is not to provide other guarantees of fairness, expediency and also legal certainty. Legal protection will be more evident in the ownership of land rights is supported by the presence of certificate of land rights, as a means of proof of land ownership rights.